2017
DOI: 10.4049/jimmunol.1601297
|View full text |Cite
|
Sign up to set email alerts
|

NKG2C/E Marks the Unique Cytotoxic CD4 T Cell Subset, ThCTL, Generated by Influenza Infection

Abstract: CD4 T cells can differentiate into multiple effector subsets, including ThCTL that mediate MHC-II restricted cytotoxicity. Although CD4 T cell mediated cytotoxicity has been reported in multiple viral infections, their characteristics and the factors regulating their generation are unclear, in part due to a lack of a signature marker. We show here that in mice, NKG2C/E identifies the ThCTL that develop in the lung during influenza A virus (IAV) infection. ThCTL express the NKG2X/CD94 complex, in particular the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 78 publications
6
69
0
Order By: Relevance
“…In addition to confirming previous observations of degranulation , we found evidence of intracellular storage of granzyme B and observed antigen‐specific cytotoxic activity, both highlighting a direct effector role of CD4 T cells in the control of HHV‐6B, as previously suggested . In other models, it has been observed that CD4 T cells may act as effector cells exerting cytotoxic activities . As previously observed , we found that infection of SupT1.CIITA cells with HHV‐6B resulted in downregulation of MHC‐class I.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to confirming previous observations of degranulation , we found evidence of intracellular storage of granzyme B and observed antigen‐specific cytotoxic activity, both highlighting a direct effector role of CD4 T cells in the control of HHV‐6B, as previously suggested . In other models, it has been observed that CD4 T cells may act as effector cells exerting cytotoxic activities . As previously observed , we found that infection of SupT1.CIITA cells with HHV‐6B resulted in downregulation of MHC‐class I.…”
Section: Discussionsupporting
confidence: 92%
“…CD4 cytotoxic T helper cells (ThCTL) have been shown to be an important effector population generated in the tissue during IAV immune responses (57, 59, 60). Generation of ThCTL depend on IL-2, but in vitro development of cytotoxicity is not IL-6 dependent (57), though in vivo requirements for IL-6 in ThCTL generation are not known.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is also possible that CD4 þ CTLs may comprise a distinct, independent subset of CD4 þ effector T cells that differ from conventional Th1 cells (10). Indeed, several recent reports have identified specific markers for CD4 þ CTLs (11)(12)(13)(14). Interestingly, Eomes is expressed in many of the cells expressing these markers, as well as in other CD4 þ T cells with cytolytic properties (15)(16)(17)(18); these findings suggested that Eomes governs development of CD4 þ CTLs and that Eomes expression is a marker for CD4 þ CTLs.…”
mentioning
confidence: 99%